A conserved hypothetical gene is required but not sufficient for Ptr ToxC production in Pyrenophora tritici-repentis. - Shi, Gongjun State; Kariyawasam, Gayan; Liu, Sanzhen; Leng, Yueqiang; Zhong, Shaobin; Ali, Shaukat; Moolhuijzen, Paula; Moffat, Caroline; Rasmussen, Jack B; Friesen, Timothy L; Faris, Justin D; Liu, Zhaohui (2022)
The fungus Pyrenophora tritici-repentis (Ptr) causes tan spot, an important foliar disease of wheat worldwide. The fungal pathogen produce three necrotrophic effectors, namely Ptr ToxA, Ptr ToxB and Ptr ToxC to induce necrosis or chlorosis in wheat. Both Ptr ToxA and Ptr ToxB are proteins, and their encoding genes have been cloned. Ptr ToxC was characterized as a low-molecular-weight molecule 20 years ago but the gene(s) controlling its production in Ptr are unknown. Here, we report the genetic mapping, molecular cloning and functional analysis of a fungal gene that is required for Ptr ToxC production. The genetic locus controlling the production of Ptr ToxC, termed as ToxC, was mapped to a subtelomeric region using segregating bi-parental populations, genome sequencing, and association analysis. Additional marker analysis further delimited ToxC to a 173 kb region. The predicted genes in the region were examined for presence/absence polymorphism in different races/isolates leading to the identification of a single candidate gene. Functional validation showed that this gene was required but not sufficient for Ptr ToxC production, thus it is designated as ToxC1. ToxC1 encoded a conserved hypothetical protein likely located on the vacuole membrane. The gene was highly expressed during infection, and only one haplotype was identified among 120 isolates sequenced. Our work suggests that Ptr ToxC is not a protein and is likely produced through a cascade of biosynthetic pathway. The identification of ToxC1 is a major first step towards revealing the Ptr ToxC biosynthetic pathway and studying its molecular interactions with host factors.